„Odpowiednie dać rzeczy słowo”, czyli świat Ryszarda Kapuścińskiego w przekładzie - Pycia, Paulina (Przekłady Literatur Słowiańskich, 2011)
„To give the proper word” — to thing, the world of Ryszard Kapuściński in translation The unique epic stories written by Kapuściński show his individual style which is the great challenge for all tranlators. This article represents some of the translation solutions in two translations of the Polish reportage Podróże z Herodotem by Ryszard Kapuściński: the Serbian one Putovanja s Herodotom by Biserka Rajčić and the English one Travels with Herodotus by Klara Główczewska. The analysis is connected mostly with the lexical layer and the metaphorical meaning of chosen phrases.